Cost-Effectiveness of Population Screening Programs for Cardiovascular Diseases and Diabetes in Low- and Middle-Income Countries: A Systematic Review - Sharma, Manushi; John, Renu; Afrin, Sadia; Zhang, Xinyi; Wang, Tengyi; Tian, Maoyi; Sahu, Kirti Sundar; Mash, Robert; Praveen, Devarsetty; Saif-Ur-Rahman, K. M. (Frontiers in Public Health, 2022)
Almost all low- and middle-income countries (LMICs) have instated a program to control and manage non-communicable diseases (NCDs). Population screening is an integral component of this strategy and requires a substantial chunk of investment. Therefore, testing the screening program for economic along with clinical effectiveness is essential. There is significant proof of the benefits of incorporating economic evidence in health decision-making globally, although evidence from LMICs in NCD prevention is scanty. This systematic review consolidates and synthesises economic evidence of screening programs for cardiovascular diseases (CVD) and diabetes from LMICs. The study protocol is registered on PROSPERO (CRD42021275806) and includes articles from English and Chinese languages. An initial search retrieved a total of 2644 potentially relevant publications. Finally, 15 articles (13 English and 2 Chinese reports) were included and scrutinised in detail. We found 6 economic evaluations of interventions targeting cardiovascular diseases, 5 evaluations of diabetes interventions, and 4 were combined interventions, i.e. screening of diabetes and cardiovascular diseases. The study showcases numerous innovative screening programs that have been piloted, such as using mobile technology for screening, integrating non-communicable disease screening with existing communicable disease screening programs, and using community health workers for screening. Our review reveals that context is of utmost importance while considering any intervention, i.e. depending on the available resources, cost-effectiveness may vary – screening programs can be made universal or targeted just for the high-risk population.